PERAN DOSEN PEMBIMBING SEBAGAI PEMIMPIN YANG MELAYANI DALAM PEMBIMBINGAN TUGAS AKHIR MAHASISWA PROGRAM SARJANA [THE ROLE OF SUPERVISOR AS A SERVANT LEADER IN THE FINAL PROJECT SUPERVISION OF UNDERGRADUATE STUDENTS] - Neneng Andriani; Budi Wibawanta (Polyglot, 2020)
The final project is a graduation requirement for undergraduate students to obtain their bachelor’s degree. The final project is carried out by students  under the direction of their supervisors. One of the indicators of a supervisor’s success in the final project supervision is that students are able to complete the final project in one semester. The supervisor is expected to be able to carry out his role by imitating Jesus Christ, in accordance with the vision and mission of Universitas Pelita Harapan as a Christian institution which prioritizes faith in Christ. This research aims to understand the role of the supervisor as a servant leader in the final project supervision. This is important in order to see how he conforms to the role and also can be used as a reference to improve the performance of the final project supervisor. A qualitative research method in a study case was used in this research to generate an in-depth understanding. Research subjects were six lecturers who participated in structured interviews and 36 student respondents who gave responses through questionnaires. Based on the results of the analysis, the supervisors in the Faculty of Psychology have carried out their role as servant leaders in their students’ final project supervision and supporting their students in completing their final projects in one semester.BAHASA INDONESIA ABSTRACT: Tugas akhir merupakan syarat kelulusan bagi mahasiswa program sarjana untuk mendapatkan gelar sarjana strata satu. Proses pengerjaan tugas akhir dilakukan oleh mahasiswa di bawah arahan dosen pembimbing, di mana salah satu indikator keberhasilan dosen pembimbing dalam proses pembimbingan tugas akhir adalah mahasiswa mampu menyelesaikan tugas akhir dalam satu semester. Dosen pembimbing diharapkan dapat menjalankan perannya dengan meneladani Yesus Kristus, sesuai dengan visi dan misi Universitas Pelita Harapan sebagai sebuah institusi Kristen yang mengedepankan iman kepada Kristus. Penelitian ini dilakukan untuk mengetahui bagaimana peran dosen pembimbing sebagai pemimpin yang melayani dalam menjalankan proses bimbingan tugas akhir. Hal ini penting untuk mengetahui kesesuaian peranan dosen pembimbing dan dapat dijadikan acuan untuk meningkatkan kinerja dosen pembimbing tugas akhir. Analisis data dilakukan dengan menggunakan metode penelitian kualitatif studi kasus untuk mendapatkan deskripsi secara mendalam. Subjek penelitian adalah enam orang narasumber dosen dengan melakukan wawancara terstruktur dan 36 responden mahasiswa yang memberikan tanggapan melalui kuesioner. Berdasarkan hasil analisis, dosen pembimbing di Fakultas Psikologi UPH telah menjalankan perannya sebagai pemimpin yang melayani dalam pembimbingan tugas akhir mahasiswa dengan baik dan mendukung mahasiswa dalam menyelesaikan tugas akhir dalam satu semester.